Dynamic coordination behavior of a structurally constrained, nucleophilic Sn(II) towards gold(I) - Ruppert, Heiko; Schreyer, Till; Dietl, Martin C.; Rudolph, Matthias; Hashmi, A. Stephen K.; Greb, Lutz (Zeitschrift für anorganische und allgemeine Chemie, 2024)
Tetradentate meso-octaalkylcalix[4]pyrroles are well-established ligands in d- and f-block chemistry. In contrast to the related porphyrins, the sp3-hybridized meso-carbon atoms linking the four pyrrole units result in highly divers coordination modes. We previously reported on the combination of this ligand system with Sn(II) centers yielding tetracoordinated stannate(II) anions which could be employed as electron-rich, strong σ-donor ligands in transition metal chemistry. With this work we are extending the coordination chemistry of meso-octaethylcalix[4]pyrrolato stannate(II) [1]2− onto gold(I). Synthesis of mono- and dinuclear gold complexes reveal a new dynamic binding mode involving μ2-bridging coordination of a pyrrole nitrogen atom to both Sn and Au. Single-crystal X-ray diffraction and variable temperature NMR spectroscopy combined with quantum mechanical computations and bond analysis tools shed light on the involved intermediates.
Gesehen am 26.11.2024